Heterogeneous immune landscapes and macrophage dynamics in primary and lung metastatic adenoid cystic carcinoma of the head and neck - Wang, Xuelian; Ma, Tingyao; Liu, Hongfei; Zhang, Shujing; Yang, Guoliang; Zhao, Yue; Kong, Lu; Gao, Ran; Chen, Xiaohong (Frontiers in Immunology, 2024)
IntroductionRecurrent or metastatic adenoid cystic carcinoma (ACC) of the head and neck is rare and highly aggressive. Due to the ineffectiveness of immune checkpoint therapies, this study aims to investigate the tumor immune microenvironment of primary tumor tissues and lung metastatic tissues and to comprehend the challenges of immunotherapy.MethodsWe analyzed RNA sequencing data and constructed immune landscapes from 25 primary tumors and 34 lung metastases. The data were then validated by immunohistochemistry and single-cell sequencing analysis.ResultsCompared to adjacent normal tissues, both primary and lung metastatic ACC showed low immune infiltration. Lung metastases had higher immune infiltration levels and antigen presentation scores but also higher T cell exclusion and dysfunction scores. Single-cell sequencing data and immunohistochemistry revealed abundant immunosuppressive tumor-associated macrophages in lung metastases. Patients with high M2 macrophage infiltration had shorter lung metastasis-free survival. DiscussionPrimary and lung metastatic ACC exhibit heterogeneous tumor immune microenvironments. Higher immune cell infiltration in lung metastases is countered by the presence of suppressive tumor-associated macrophages, which may limit effective anti-tumor responses.